2015
DOI: 10.1063/1.4906149
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous curvature of bilayer membranes from molecular simulations: Asymmetric lipid densities and asymmetric adsorption

Abstract: Biomimetic and biological membranes consist of molecular bilayers with two leaflets which are typically exposed to different aqueous environments and may differ in their molecular density or composition. Because of these asymmetries, the membranes prefer to curve in a certain manner as quantitatively described by their spontaneous curvature. Here, we study such asymmetric membranes via coarse-grained molecular dynamics simulations. We consider two mechanisms for the generation of spontaneous curvature: (i) dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 54 publications
12
124
1
Order By: Relevance
“…However, this mechanism alone cannot significantly affect the λ-value. On the other hand, recent work has shown that an asymmetry in the nature of fluids surrounding the bilayer can also influence the curvature-density coupling, even in the case of a single-component membrane [40]. Moreover, spontaneous curvature can be generally taken into account using a term similar to the coupling term in Eq.…”
Section: Vesicle Free Energymentioning
confidence: 99%
“…However, this mechanism alone cannot significantly affect the λ-value. On the other hand, recent work has shown that an asymmetry in the nature of fluids surrounding the bilayer can also influence the curvature-density coupling, even in the case of a single-component membrane [40]. Moreover, spontaneous curvature can be generally taken into account using a term similar to the coupling term in Eq.…”
Section: Vesicle Free Energymentioning
confidence: 99%
“…In our particle-based model, each of the chains consists of six beads of type C and the head group is built up from three beads of type H. The non-adhesive particles are represented by single beads of type P. As in our previous simulation study, 3 we take all beads, including the particle beads, to have the same diameter d, which is convenient from a computational point of view. Furthermore, the separation of the two head group layers is about 5d.…”
Section: A Dissipative Particle Dynamicsmentioning
confidence: 99%
“…For lipid bilayers, this separation has a typical value of 4 nm which implies that the bead diameter d ≃ 4 nm/5 = 0.8 nm. 3 The interactions between the DPD beads are parametrized in the usual form, 3,21,25 the corresponding DPD parameters a i j are given in Table II. These parameters describe the strength of the repulsive forces between the soft-core particles.…”
Section: A Dissipative Particle Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two opposing forces, interfacial tension and steric repulsion, produce the inhomogeneous stress inside the bilayers [19]. This inhomogeneity is a key property of the bilayers because it determines the area per lipid molecule [19], spontaneous curvature [20][21][22][23][24], Gaussian curvature modulus [21][22][23][24][25][26][27][28], and function of the mechanosensitive channel [29,30]. Since the stress profile cannot be obtained experimentally [31,32], estimation using molecular simulations is important.…”
Section: Introductionmentioning
confidence: 99%